A comparative study on behavior of heavy metals in pyrochar and hydrochar from sewage sludge. Issue 5 (4th March 2018) - Chen, Hongmei; Zhou, Yanli; Zhao, Haihua; Li, Qing
ABSTRACT: Behavior of heavy metals in biochar obtained from sewage sludge with the pyrolysis and hydrothermal processes was comparatively studied. Increase of reaction temperature resulted in increased pH of pyrochar (7.75 ~ 8.96) and hydrochar (5.94 ~ 7.00), while yields of pyrochar and hydrochar were both decreased. For hydrochar, temperature higher than 300 was found to be adverse to the immobilization of Cu and Zn. In comparison with hydrothermal process, increase of reaction temperature in the pyrolysis process was beneficial to the immobilization of Cu and Pb, while adverse effect was found on Cd and Zn.